1995
DOI: 10.1002/cne.903550204
|View full text |Cite
|
Sign up to set email alerts
|

Glial cells of the lamprey nervous system contain keratin‐like proteins

Abstract: Lamprey axons regenerate following spinal cord transection despite the formation of a glial scar. As we were unable to detect a lamprey homologue of glial fibrillary acidic protein (GFAP), a major constituent of astrocytes, we studied the composition of intermediate filament (IF) proteins of lamprey glia. Monoclonal antibodies (mAbs) were raised to lamprey spinal cord cytoskeletal extracts and these mAbs were characterized by using Western blotting and immunocytochemistry. On two-dimensional (2-D) Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…The ependyma was mostly free of D-serine immunoreactivity, and no positive cells of the same size and appearance of lamprey astrocytes (see Merrick et al, 1995) were observed. The distribution of D-serine-ir cells in the different brain regions of adult lamprey brain is described first, and, where appropriate, the colocalization of D-serine with GABA immunoreactivity in neurons is also indicated.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The ependyma was mostly free of D-serine immunoreactivity, and no positive cells of the same size and appearance of lamprey astrocytes (see Merrick et al, 1995) were observed. The distribution of D-serine-ir cells in the different brain regions of adult lamprey brain is described first, and, where appropriate, the colocalization of D-serine with GABA immunoreactivity in neurons is also indicated.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, expression of glycine and GABA immunoreactivity in lamprey brain perikarya is largely maintained from larvae to adulthood (Villar-Cerviño et al, 2009), indicating that lampreys are highly useful for investigating the neuronal distribution of amino acid neurotransmitters in the brain. With regard to the glia, lampreys lack oligodendrocytes, and glial cells of the brain are ependymal tanycytes or small astrocytes (Merrick et al, 1995), which may greatly facilitate the identification of cells containing D-serine.…”
mentioning
confidence: 99%
“…To identify candidates for this missing protein, we surveyed 43 mAbs designated as LCM series, which were generated previously against cytoskeletal proteins of the lamprey nervous system by Merrick et al (1995) in this laboratory. Seven LCMs were neuron specific, and five were glial specific, as demonstrated by immunohistochemistry (described later).…”
Section: Identification Of Neuron-specific Monoclonal Antibodies To Lmentioning
confidence: 99%
“…Therefore, its electrophoretic labeling pattern was compared with those of LCM3 and LCM39 on Western blots, and all of these were compared with the electrophoretic pattern of LCM1, a mAb previously determined to be specific for lamprey glial keratins (Merrick et al, 1995) (Fig. 2).…”
Section: Comparisons Of Four Lcm Monoclonal Antibodies In Western Blotmentioning
confidence: 99%
See 1 more Smart Citation